¿Las indemnizaciones adicionales en los casos de extinción del contrato de trabajo a las reguladas en el Estatuto de los Trabajadores son válidas? Are additional compensations in cases of termination of the employment contract to those regulated in the Workers’ Statute legal? - García Viña, Jordi (LABOS Revista de Derecho del Trabajo y Protección Social, 2023)
In labor regulations there are various cases in which the employer must pay certain compensation for his or her conduct, especially in cases of termination of the employment contract where since 1980 there has been a regulation based on an objective and predetermined scale, according to the salary and seniority of the employee. Since the pandemic and because of the specific regulation, various courts have considered the possibility of granting additional compensation, understanding that the legal compensation assessed is not sufficiently dissuasive. The courts, based on conventionality control, have applied the art. 24 of the European Social Charter (revised), as well as the interpretation by the European Committee of Social Rights of the Council of Europe. However, only a ruling by the Superior Court of Justice of Catalonia dated January 30, 2023,has granted additional compensation.